Childhood neurodevelopmental outcomes of survivors of acute bilirubin encephalopathy: A retrospective cohort study - Kumar, Vinod; Kumar, Praveen; Sundaram, Venkataseshan; Munjal, Sanjay Kumar; Malhi, Prahbhjot; Panda, Naresh Kumar (Early human development, 2021)
Reports on childhood neurodevelopmental and neurosensory outcomes following acute bilirubin encephalopathy from low- and middle-income countries are scarce. This study aimed to analyze the neurodevelopmental and neurosensory outcomes of survivors of acute bilirubin encephalopathy. Retrospective cohort. Neonates with admission diagnosis of acute bilirubin encephalopathy were followed up and assessed for neuromotor, neurodevelopmental and neurosensory functions between 18 m and 12.5 years of age. In 67 neonates with acute bilirubin encephalopathy, a composite outcome of cerebral palsy or death was observed in 33 (49%) subjects. Choreo-athetoid cerebral palsy [19 (73%)] was the most common type observed. Sensori-neural hearing loss was observed in 46 (79%) subjects. Subjects with cerebral palsy had significantly low Developmental profile-3 scores in all assessed domains. Neonates with an early-stage acute bilirubin encephalopathy (aOR (95% C.I): 0.12 (0.05–0.71); p = 0.02) and those with a normal neurological examination at discharge (aOR (95% C.I): 0.11 (0.06–0.7); p = 0.049) had significantly lower odds of the primary outcome. Majority of survivors of acute bilirubin encephalopathy had adverse outcomes during childhood in the form of cerebral palsy and sensory-neural hearing loss. Cognitive functions were better preserved than the language and general development in the affected children. •Systematic data of childhood neurodevelopmental outcomes in survivors of acute bilirubin encephalopathy is reported•Half and three-fourths of survivors of acute bilirubin encephalopathy, respectively, had cerebral palsy and sensori-neural hearing loss during their childhood•Cognitive functions were better preserved than the language and general development in the affected children.•Advanced stage of ABE and an abnormal neurological examination at discharge were independent predictors of CP or death at later point in age.